Knowledge and attitude of Al-Ghad college students towards corona virus infection - M. Hassan, Haytham (International Journal of Medical Research and Review, 2016)
Objective: This study was conducted to identify the knowledge, attitudes and beliefs towards Corona virus infection among students in Al-Ghad International College for Applied Medical Science in Riyadh Male Campus. Methods: Using a descriptive cross-sectional method, data were collected from 220 sample students, using a simplified, structured, self-administered questionnaire, including closed questions completed by students in their classes. Results: The findings indicate that most students gave correct answers to questions related to disease prevention and control while the lowest percent was observed in questions related to mode of transmission, whereas questions related to the general knowledge about corona virus and the clinical picture of disease have intermediate percents of correct answers. Students’ knowledge status was positively associated with their age category. Most of the students get their information about the corona virus from websites (internet) followed by TV and friends. Also, most of the students agreed that corona is a fatal virus and it’s dangerous to the community, diseased people must be isolated, health education campaigns decrease the virus transmission and the necessary measures for disease control were taken by the responsible authority. Conclusion: This study gives an idea about the effect of interventional activities against corona virus infection and areas that needs further efforts to control the spread of the virus transmission.